2011
DOI: 10.1002/jbio.201000051
|View full text |Cite
|
Sign up to set email alerts
|

On the sensitivity of forward scattering patterns from bacterial colonies to media composition

Abstract: Morphology of colonies is important for taxonomy and diagnostics in microbiology where the response to environmental factors is sensitive enough to support discrimination. In this research, we analyzed the forward scattering patterns of individual Escherichia coli K12 colonies when agar hardness and nutrition levels were varied from the control sample. As the agar concentration increased from 1.2% to 1.8%, the diameter of the forward scattering patterns also increased for the same experimental condition which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 36 publications
4
34
0
Order By: Relevance
“…The ability of BARDOT to distinguish bacterial colonies was further strengthened when scatter patterns of the lap mutant strain were shown to be distinct from those of the WT on both BHIA and LBA, though the biophys- ical properties (colony height, diameter, transmittance, and reflectance) remained unchanged. This finding is in congruence with a previous study in which changes in the LB medium composition (agar and yeast extract concentrations) were also found to affect the growth morphologies and scatter patterns of E. coli colonies (48).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The ability of BARDOT to distinguish bacterial colonies was further strengthened when scatter patterns of the lap mutant strain were shown to be distinct from those of the WT on both BHIA and LBA, though the biophys- ical properties (colony height, diameter, transmittance, and reflectance) remained unchanged. This finding is in congruence with a previous study in which changes in the LB medium composition (agar and yeast extract concentrations) were also found to affect the growth morphologies and scatter patterns of E. coli colonies (48).…”
Section: Discussionsupporting
confidence: 82%
“…The scatter patterns of both WT and lap mutant strains on BHIA were different from the scatter patterns on LBA. This finding is in congruence with a previous study in which changes in the LB medium composition (agar and yeast extract concentrations) were also found to affect the morphologies and scatter patterns of E. coli colonies (48).…”
Section: Lap Expression Affects the Scatter Patterns Of L Monocytogesupporting
confidence: 82%
“…In their study it was observed that Bacillus colony under extreme air-drying condition (7% agar) grew more vertically compared to less drying condition (1% agar), where colony grew more laterally. Such variation in colony profile will impart immense difference in BARDOT scatter patterns based on physical theoretical variations of light forward scattering as mentioned in our previous studies [18,27]. This may be the reason for the irreproducible and incongruent scatter patterns under extreme drying condition, when compared to short drying condition.…”
Section: Extreme Air-drying Conditionsmentioning
confidence: 82%
“…But the major issue with the BARDOT-based sensor is to obtain consistent patterns since many parameters could influence the scatter signatures, like agar concentration, media formulations, and nutrient levels [10,18]. Thus, the goal of this study was to investigate if different preparation methods and storage conditions of agar plate, such as moisture level, air-drying times, storage temperature, and duration of agar plate storage that are generally practiced in a microbiology laboratory, affect the colony scatter signatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation